Students’ social representations about world culture - E. V. Zvonova; A. S. Gruzdeva (Вестник университета)
The relevance of the problem under study stems from the interest that social representations have in modern science, as well as the role of students in the development of the modern world. The aim of the article is to present the results of the study of the structure of social perceptions of culture among Russian and American students, statistical and qualitative analysis of the results obtained. The findings suggest that there are differences in the concepts that American and Russian students are willing to designate as categories reflecting their perceptions of world culture. Both groups of students include the general concept of art in the content of the scheme of social representation of world culture, but Russian students are most active in indicating components that focus on revealing the inner world of an individual. The notions given by American students about world culture reflect its importance as an area for active intercultural communication. The materials of this article may be useful for further research into the main factors of globalisation processes, as well as for understanding the subsequent development of the content and structure of young people’s social perceptions.